Peran Pemerintah dan Masyarakat Dalam Mewujudkan Pembangunan Berkelanjutan: Studi Kasus di Indonesia - Zuldani, Irwan; Umar, Genius; Dewata, Indang (PT Hakhara Akademia Indonesia, 2025)
Sustainable development in Indonesia is a complex challenge that requires close collaboration between government, communities, and the private sector. This article examines the critical role of government policies and regulations in supporting or hindering the achievement of sustainable development goals. Through an analysis of factors including community participation, communication, and collaboration, the article identifies existing barriers and effective forms of community participation in natural resource management. In addition, lessons learned from successful local initiatives demonstrate the importance of community engagement, environmental education, and technological innovation. Proposed strategies to address these challenges include improving communication, encouraging community involvement, building strong partnerships, and adopting environmentally friendly technologies. By adopting an integrated and collaborative approach, it is hoped that the sustainable development goals can be achieved, creating a more inclusive and sustainable future for future generations.